Analisis Sertifikasi Pelaut, Keterampilan, dan Kesejahteraan Awak Kapal Sebagai Variabel Mediasi Terhadap Kinerja Operasional Kapal - Ivan - Potto; Sri - Handayani; Yana - Tatiana; Prasadja - Ricardianto (Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2022)
Analysis Of Seafarer Certification, Skills Ship Crew, And Ship Crew's Welfare As Mediation Variables Against Ship Operational Performance. This study aims to determine the effect of certification, skills, and welfare of the crew on the operational performance of ships at PT Amas Samudra Jaya. This study uses quantitative methods, with the number of samples based on the Slovin formula of as many as 100 respondents. Collecting data in the form of a statement sheet with a Likert scale model. To solve the problems the authors, use two methods of data collection, namely, field data (field research) and library data. Both methods of data analysis use path analysis with the Smartpls3 SEM model. The results of the analysis and discussion show that the first hypothesis has a significant positive direct effect on seafarers' certification on the welfare of crew members. Second, there is a significant positive direct effect of crew skills on the welfare of crew members. Third, there is a significant positive direct effect of seafarers' certification on the operational performance of ships. Fourth, there is a significant positive direct effect of crew skills on ship operational performance. Fifth, there is a significant positive direct effect on the welfare of the crew on the ship's operational performance. Sixth, the welfare of the crew can mediate seafarers' certification of the ship's operational performance. Seventh, the welfare of the crew can mediate the skills of the crew on the operational performance of the ship.Keywords: Seafarers Certification, Crew Skills, Crew Welfare, Ship Operational Performance